Characterization of Dimorphism in Cladosporium werneckii - Hardcastle, Ronald V. (1974)
Yeast forms of the dimorphic fungus Cladosporium werneckii grow by polar budding and yield a homogeneous yeast phase when cultured at 21 C in an agitated sucrose-salts medium (Czapek-Dox broth). Yeast extract enrichment of such a yeast phase consisting of 10(4) yeasts per ml induces a quantitative conversion of the yeasts to true hyphae. This conversion is not mediated by a transition cell and is often attended by capsule formation. When 10(5) or 10(6) yeasts per ml receive enrichment, a nonquantitative conversion to moniliform hyphae is effected and no capsule formation is observed. Rapid agitation compared to slow agitation or stationary incubation of the nutritionally mediated conversion cultures greatly accelerates the production of lateral hyphal buds or their yeast progenies. These cells appear incapable of undergoing nutritional conversion to hyphae, but instead must grow for several generations in the unenriched sucrose-salts medium to restore conversion competence. Temperature shifts affect directly the morphology and morphogenesis of the yeast in unenriched medium; at 17 C yeasts are smaller and more ovoid than at 21 C, and at 30 C marked conversion of yeasts to moniliform hyphae occurs. A methodology employing the Coulter counter and Coulter channelizer provides evidence that direct correlations do not always exist between the optimum conditions for the growth of C. werneckii and the optimum conditions for its yeast-to-mold conversion.